Inheritance of traits related to fruit shape and color in african eggplant (Research, Society and Development, 2022)
The African eggplant is a solanaceous vegetable with bitter tasting immature fruit of various colors (light green, dark green, white) and shapes (from elongated to round). Because it is a little known vegetable, there are few studies on the inheritance of its economically important traits.  The objective of this work had was to study the inheritance of shape and immature fruit color in S. gilo, in order to assist future breeding programmes with this crop. Cultivars Morro Redondo (MR, with dark green round fruit) and Comprido Verde Claro (CVC, with elongated light green fruit) were tested alond with their F1(MR x CVC), F2(MRxCVC), BC11[MRx(MRxCVC)],  and BC12[CVCx(MRxCVC) generations.  A test based on maximum likelihood was used to test the hypothesis of monogenic control fruit length (L), diameter (D) and L/D ratio. Fruit diameter was under control of a major gene locus with additive effects, plus polygenes also with additive effects.  Fruit length and L/D ratio were under control of polygenes with predominantly additive effects. Fruit color was determined by a major gene locus with two alleles, with dominance of the allele that controls dark green over light green color, but there was also evidence for the presence of modifier genes.